2015
DOI: 10.1016/j.dcn.2015.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Auditory attention in childhood and adolescence: An event-related potential study of spatial selective attention to one of two simultaneous stories

Abstract: Auditory selective attention is a critical skill for goal-directed behavior, especially where noisy distractions may impede focusing attention. To better understand the developmental trajectory of auditory spatial selective attention in an acoustically complex environment, in the current study we measured auditory event-related potentials (ERPs) in human children across five age groups: 3–5 years; 10 years; 13 years; 16 years; and young adults using a naturalistic dichotic listening paradigm, characterizing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 94 publications
(166 reference statements)
3
30
0
Order By: Relevance
“…However, in studies using the dichotic listening paradigm described above, the selective attention effect has been observed as positive in amplitude in early childhood, mimicking the morphology of the auditory ERPs that are positive in amplitude for the probes in both the attended and the unattended stories in young children. As discussed in previous studies (24,25,27), we argue that this difference in morphology mainly stems from the maturation of the auditory cortex and that the selective attention effect that emerges around 100 ms in children reflects a developing early selection and sensory gain mechanism.…”
Section: Significancesupporting
confidence: 61%
“…However, in studies using the dichotic listening paradigm described above, the selective attention effect has been observed as positive in amplitude in early childhood, mimicking the morphology of the auditory ERPs that are positive in amplitude for the probes in both the attended and the unattended stories in young children. As discussed in previous studies (24,25,27), we argue that this difference in morphology mainly stems from the maturation of the auditory cortex and that the selective attention effect that emerges around 100 ms in children reflects a developing early selection and sensory gain mechanism.…”
Section: Significancesupporting
confidence: 61%
“…Auditory selective attention task. We used the same auditory attention ERP paradigm as our previous studies with child and adult participants (Karns, Isbell, Giuliano, & Neville, 2015;Neville et al, 2013;Stevens et al, 2009;Sanders et al, 2006;Coch et al, 2005). Participants were cued to selectively attend to one of two simultaneously presented children's stories differing in location (left/right loudspeaker), narrator's voice (a male or female reading the entire story aloud), and content.…”
Section: Methodsmentioning
confidence: 99%
“…Task demands involve sitting still and listening to a narrator within a crowded auditory environment, much like one might be asked to do within an academic or professional context, or even when enjoying leisure time activities. A number of studies have demonstrated that this task is suitable for measuring selective attention from three years of age to adulthood (Karns, Isbell, Giuliano, & Neville, 2015;Sanders. Stevens, Coch, & Neville, 2006), including samples at risk for chronic stress exposure and from lower socioeconomic status backgrounds (Neville et al, 2013;Stevens, Lauinger, & Neville, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…We used the same auditory attention ERP paradigm as our previous studies with child and adult participants (Coch, Sanders, & Neville, 2005;Karns et al, 2015;Neville et al, 2013;Sanders et al, 2006;Stevens et al, 2009). Participants were cued to selectively attend to one of two simultaneously presented children's stories differing in location (left/right loudspeaker), narrator's voice (a male or female reading the entire story aloud), and content.…”
Section: Auditory Selective Attention Taskmentioning
confidence: 99%
“…Task demands involve sitting still and listening to a narrator within a crowded auditory environment, much like common academic, professional, and leisure time contexts. This task is a reliable index of selective attention from 3 years of age to adulthood (Karns, Isbell, Giuliano, & Neville, 2015;Sanders, Stevens, Coch, & Neville, 2006), including samples from lower socioeconomic status (SES) backgrounds (Neville et al, 2013;Stevens, Lauinger, & Neville, 2009).…”
Section: Introductionmentioning
confidence: 99%